Layered metal carbo–selenide Nb2CSe2 with van der Waals interlayer coupling - Junchao Wang; Renfei Cheng; Tao Hu; Xinyue Tang; Yan Liang; Min Tian; Ting Xiong; Qiuhong Lu; Qi Zhu; Zhiqing Yang; Xiaohui Wang; Yanchun Zhou (Journal of Advanced Ceramics)
The stacking structure of Nb2CSe2, a newly synthesized layered metal carbo-selenide, was elucidated by scanning transmission electron microscopy. Nb2CSe2 features Se−Nb−C−Nb−Se quintuple atomic layers. These layers are stacked in Bernal mode. In this mode, Nb2CSe2 crystallizes in a trigonal symmetry (space group P3¯m1, No. 164), with lattice parameters of a = 3.33 Å and c = 18.20 Å. Electronic structure calculations indicate that the metal carbo-selenide has Fermi energy crossing the bands where it touches to give a zero gap, indicating that it is an electronic conductor. As evidenced experimentally, the electrical conductivity is as high as 6.6×105 S·m−1, outperforming the counterparts in the MXene family. Owing to the layered structure, the bonding in Nb2CSe2 with an ionic formula of (Nb1.48+)2(C1.74−)(Se0.61−)2 is highly anisotropic, with metallic–covalent–ionic bonding in intralayers and weak bonding between interlayers. The layered nature is further evidenced by elastic properties, interlayer energy, and friction coefficient determination. These characteristics indicate that Nb2CSe2 is an analog of molybdenum disulfide (MoS2), which is a typical binary van der Waals (vdW) solid. Moreover, vibrational properties are reported, which may offer an optical identification standard for new ternary vdW solids in spectroscopic studies, including Raman scattering and infrared absorption.